2019
DOI: 10.1007/s00520-019-4643-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of controlled-release oxycodone for reducing pain due to oral mucositis in nasopharyngeal carcinoma patients treated with concurrent chemoradiotherapy: a prospective clinical trial

Abstract: Background Pain due to oral mucositis (OM) is a major problem during concurrent chemoradiotherapy (CCRT) in nasopharyngeal carcinoma (NPC) patients. Methods We enrolled 56 NPC patients receiving CCRT and allocated them into two groups: moderate pain group ( n = 27) and a severe pain group ( n = 29) according to the degree of pain reported (moderate = numerical rating scale (NRS) score 4–6 or severe = NRS score 7–10) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Extra toxicity can also lead to a poor quality of life. 8 Therefore, identifying the patient or tumor characteristics associated with toxicity and survival can potentially help personalize treatment regimens and improve the quality of care in patients with NPC. Depletion of skeletal muscle mass, termed sarcopenia, is common in head and neck cancer (HNC), and is related to increased treatment-related toxicity and decreased survival in HNC patients who receive comprehensive treatment of surgery/chemotherapy and/or radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Extra toxicity can also lead to a poor quality of life. 8 Therefore, identifying the patient or tumor characteristics associated with toxicity and survival can potentially help personalize treatment regimens and improve the quality of care in patients with NPC. Depletion of skeletal muscle mass, termed sarcopenia, is common in head and neck cancer (HNC), and is related to increased treatment-related toxicity and decreased survival in HNC patients who receive comprehensive treatment of surgery/chemotherapy and/or radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…According to the evidence-based clinical practice guidelines on mucositis published by the mucositis research group of the Multinational Association of support Care in Cancer/International Society of Oral Oncology (MASCC/ISOO), morphine mouthwash and doxepin mouthwash are recommended for HNC patients undergoing RT ( 33 , 56 , 57 ). Studies have also shown that introduction of low-dose controlled-release oxycodone in the early stage of moderate pain in patients with RT and chemotherapy for nasopharyngeal cancer can help to reduce total dose, provide better pain control, reduce weight loss, and improve quality of life ( 58 60 ). Anti-inflammatory therapy is also a common clinical treatment.…”
Section: Clinical Intervention For Riom and Malnutrition In Hnc Patiementioning
confidence: 99%
“…Written informed consent was obtained from all subjects participating in the trial. The trial was registered prior to patient enrollment at chictr.org.cn (ChiCTR-IOR-16010032, Principal investigator: Qulian Guo, Date of registration: 2016- [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Participantsmentioning
confidence: 99%
“…The pain intensity was measured using the VAS. A decrease in VAS score of more than 25% compared with the baseline was used as an indicator of analgesic efficacy [15]. The VAS score was also compared between groups E and C at all timepoints to determine any differences in the efficacy and duration of the analgesic effects.…”
Section: Primary Outcomementioning
confidence: 99%